Side-effects of intravenously versus intramuscularly oxytocin for postpartum hemorrhage: a systematic review and meta-analysis of randomized controlled trials - Ai, Wen; Zeng, Yanfei; Zhen, Manhua; Lao, Li; Ma, Yubo; Liu, Li; Zhang, Yinghui (Frontiers in Pharmacology, 2023)
Background Oxytocin is the gold standard uterotonic agent for prevention of postpartum hemorrhage. However, there is no consensus with clear evidence about the side-effects of oxytocin administered intravenously or intramuscularly for management of the third stage of labor. We conducted a systematic review and meta-analysis of randomized controlled trials to evaluate the side-effects of intravenously or intramuscularly oxytocin for preventing postpartum hemorrhage in the third stage of labor. Methods Six representative databases were searched from the inception to July 2023. Randomized controlled trials which explored the intravenously and intramuscularly oxytocin and provided at least one side-effect were included. Statistical analysis included random or fixed-effect meta-analyses using relative risk. Results Nine studies included, involving 8295 participants. Ten types of side-effects were reported. There was no statistical difference in hypotension (RR=1.01, 95%CI=0.88-1.15), anemia (0.98, 0.83-1.15), tachycardia (0.90, 0.69-1.17), shivering (0.90, 0.69-1.17), headache (0.86, 0.31-2.37), nausea (0.70, 0.20-2.42), vomiting (0.97, 0.26-3.58), uvular edema (0.82, 0.23-2.91), diarrhea (0.97, 0.26-3.58), and fever (0.97, 0.26-3.58) between intravenously or intramuscularly groups. Conclusion There are no significant differences of side-effects between intravenously and intramuscularly administration of oxytocin for preventing postpartum hemorrhage in the third labor.